Provision of digital devices and internet connectivity to improve synchronous telemedicine access in the U.S.: a systematic scoping review - Bell, Joshua; Gottlieb, Laura M.; Lyles, Courtney R.; Nguyen, Oanh Kieu; Ackerman, Sara L.; De Marchis, Emilia H. (Frontiers in Digital Health, 2024)
IntroductionThe COVID-19 pandemic led to a dramatic increase in telemedicine use for direct patient care. Inequities in device/internet access can limit the extent to which patients can engage with telemedicine care and exacerbate health disparities. In this review, we examined existing literature on interventions designed to improve patient telemedicine access by providing digital devices including tablets, smartphones, and computers and/or internet connectivity.MethodsIn this systematic scoping review, we searched four databases for peer-reviewed studies published 1/1/2000–10/19/2021 that described healthcare interventions that provided patients with devices and/or internet connectivity and reported outcomes related to telemedicine access and/or usage. Data extraction elements included: study population, setting, intervention design, details on device/connectivity provision, and outcomes evaluated.ResultsTwelve articles reflecting seven unique interventions met inclusion criteria. Ten articles examined telemedicine utilization (83%) and reported improved patient show rates/utilization. Seven articles examined patient satisfaction with the interventions (58%) and reported positive experiences. Fewer articles examined health outcomes (17%; 2/12) though these also demonstrated positive results. Across included studies, study quality was low. There were no controlled trials, and the most rigorously designed studies (n = 4) involved pre/post-intervention assessments.DiscussionFindings from this review indicate that providing material technology supports to patients can facilitate telemedicine access, is acceptable to patients and clinicians, and can contribute to improved health outcomes. The low number and quality of existing studies limits the strength of this evidence. Future research should explore interventions that can increase equitable access to telemedicine services.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=183442, identifier, PROSPERO: CRD42020183442.